Dimethyl 4-(4-ethoxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title molecule, C(19)H(23)NO(5), the dihedral angle formed by the benzene ring and the planar part of the dihydropyridine ring is 83.52 (5)°. The dihydropyridine ring adopts a flattened boat conformation. In the crystal, molecules are linked by N—H⋯O hydrogen bonds, generating chains running parallel to [100]. The crystal structure is consolidated by C—H⋯O contacts.